Mac OS X for Unix geeks - Jepson, Brian, 1967- (O'Reilly, 2002)
If you're one of the many Unix developers drawn to Mac OS X for its BSD core, you'll find yourself in surprisingly unfamiliar territory. Even if you're an experienced Mac user, Mac OS X is unlike earlier Macs, and it's radically different from the Unix you've used before, too. Enter "Mac OS X for Unix Geeks" by Brian Jepson and Ernest E. Rothman, two Unix geeks who found themselves in the same place you are. Their new book is your guide to figuring out the BSD Unix system and Mac-specific components that are making your life difficult and to help ease you into the Unix inside Mac OS X. This concise book includes such topics as: A quick overview of the Terminal application Understanding Open Directory (LDAP) and NetInfo Issues related to using the GNU C Compiler 9GCC Library linking and porting Unix software An overview of Mac OS X?s filesystem and startup processes Creating and installing packages using Fink Building the Darwin kernel Running X Windows on top of Mac OS XThe book wraps up with a quick manpage-style reference to the "Missing Manual Pages"--Commands that come with Mac OS X although there are no manpages. If you find yourself disoriented by the new Mac environment, Mac OS X for Unix Geeks can help you acclimate yourself quickly to the familiar, yet foreign, Unix landscape.